On using Aryabhatta Remainder Theorem to Decrypt a Message with RPrime and Rebalanced RSA - J.L. Padmaja, Ch; S.Bhagavan, V; Srinivas, B (International Journal of Engineering and Technology, 2018)
RSA is the most world widely used asymmetric cryptosystem for network transactions. Through this article, we propose a new implementation of Aryabhatta Remainder theorem (ART) in place of the existing Chinese Remainder Theorem (CRT) to solve congruencies in the decryption phase for the faster variants of RSA such as RPrime RSA and Rebalanced RSA. Through our observations, we prove that using ART for CRT has improved the overall decryption speed of RPrime and Rebalanced RSA.Â Â